Recording γ-secretase activity in living mouse brains - Hou, Steven S; Ikegawa, Yuya; Kwon, Yeseo; Wieckiewicz, Natalia; Houser, Mei CQ; Lundin, Brianna; Bacskai, Brian J; Berezovska, Oksana; Maesako, Masato (eLife, 2024)
γ-Secretase plays a pivotal role in the central nervous system. Our recent development of genetically encoded Förster resonance energy transfer (FRET)-based biosensors has enabled the spatiotemporal recording of γ-secretase activity on a cell-by-cell basis in live neurons in culture. Nevertheless, how γ-secretase activity is regulated in vivo remains unclear. Here, we employ the near-infrared (NIR) C99 720–670 biosensor and NIR confocal microscopy to quantitatively record γ-secretase activity in individual neurons in living mouse brains. Intriguingly, we uncovered that γ-secretase activity may influence the activity of γ-secretase in neighboring neurons, suggesting a potential ‘cell non-autonomous’ regulation of γ-secretase in mouse brains. Given that γ-secretase plays critical roles in important biological events and various diseases, our new assay in vivo would become a new platform that enables dissecting the essential roles of γ-secretase in normal health and diseases.
Keywords: γ-secretase; biosensor; FRET; Förster resonance energy transfer; in vivo